Pandemic-Informed Proxemics: Working Environment Shifts Resulting from COVID-19 - McDonald, Caitlin E. (2020)
ABSTRACT As COVID-19 continues to disrupt our ways of working and living, organizations would do well to consider how spatial relationships (proxemics) will impact communication, formal and informal knowledge networks, and relationship-building in both physical and virtual relationships. Based on novel research from a workplace ethnography conducted in 2019, this paper will outline why the proxemics zones that anthropologist Edward T Hall pioneered in the 1960s are still so important to communication in both physical and in digitally mediated settings today. We will conclude by providing practical guidance on how organizations can put their understanding of the importance of proxemics for facilitating communication into practice in working environments, both virtual and physical, which continue to be impacted by the ongoing effects of the current pandemic. Keywords proxemics, pandemic, COVID-19, virtual working, remote working, collaboration, personal space, digitally mediated communications, knowledge networks, relationship-building ABOUT THE AUTHOR/S Dr. Caitlin E. McDonald Leading Edge Forum caitlin.mcdonald@leadingedgeforum.com Dr. Caitlin McDonald is the LEF’s resident Digital Anthropologist. She helps business leaders and teams learn to step outside their version of ‘normal,’ suspend judgement, and consider things from many different perspectives. This gives businesses the leading edge through boosting customer empathy, finding new solutions to old problems, and enriching the insight power of big data through multidisciplinary approaches. https://leadingedgeforum.com/researcher/caitlin-mcdonald/ New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s)